2015
DOI: 10.1093/molbev/msv099
|View full text |Cite
|
Sign up to set email alerts
|

Relaxing the Molecular Clock to Different Degrees for Different Substitution Types

Abstract: Rates of molecular evolution can vary over time. Diverse statistical techniques for divergence time estimation have been developed to accommodate this variation. These typically require that all sequence (or codon) positions at a locus change independently of one another. They also generally assume that the rates of different types of nucleotide substitutions vary across a phylogeny in the same way. This permits divergence time estimation procedures to employ an instantaneous rate matrix with relative rates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Typically, neither is directly observed. Lee et al [8] estimated these sufficient statistics by sampling endpoint-conditioned histories using context-independent substitution models and assuming these histories well approximated a sample of endpoint-conditioned histories from a context-dependent model. Simulation suggested that this approach was reasonable for the primate data analysed by Lee et al [8].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Typically, neither is directly observed. Lee et al [8] estimated these sufficient statistics by sampling endpoint-conditioned histories using context-independent substitution models and assuming these histories well approximated a sample of endpoint-conditioned histories from a context-dependent model. Simulation suggested that this approach was reasonable for the primate data analysed by Lee et al [8].…”
Section: Methodsmentioning
confidence: 99%
“…Lee et al [8] estimated these sufficient statistics by sampling endpoint-conditioned histories using context-independent substitution models and assuming these histories well approximated a sample of endpoint-conditioned histories from a context-dependent model. Simulation suggested that this approach was reasonable for the primate data analysed by Lee et al [8]. If we assume that endpoint-conditioned context-independent histories are a good approximation of context-dependent histories, then the sufficient statistics f b(k)j and n kj can be approximated by their sample means among histories.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations